Preparation of silver nanoparticles in virgin coconut oil using laser ablation - Zamiri, Reza; Zakaria, Azmi; Sadrolhosseini, Amir Reza; Ahangar, Hossein Abbastabar; Abd. Wahab, Zaidan; Mahdi, Mohd Adzir (Dove Medical Press, 2011)
Laser ablation of a silver plate immersed in virgin coconut oil was carried out for fabrication of silver nanoparticles. A Nd:YAG laser at wavelengths of 1064 nm was used for ablation of the plate at different times. The virgin coconut oil allowed formation of nanoparticles with well-dispersed, uniform particle diameters that were stable for a reasonable length of time. The particle sizes and volume fraction of nanoparticles inside the solutions obtained at 15, 30, 45 min ablation times were 4.84, 5.18, 6.33 nm and 1.0 × 10−8, 1.6 × 10−8, 2.4 × 10−8, respectively. The presented method for preparation of silver nanoparticles in virgin coconut oil is environmentally friendly and may be considered a green method.